2012
DOI: 10.1353/pla.2012.0040
|View full text |Cite
|
Sign up to set email alerts
|

Employment Opportunities for New Academic Librarians: Assessing the Availability of Entry Level Jobs

Abstract: This study examines the availability of entry level positions in academic libraries to better illuminate the status of the job market for current students and recent graduates of Library & Information Science programs. Over a twelve month period from 2010-2011, 1385 job advertisements were collected, with content analysis methods used to evaluate each advertisement by level of position, institution type, location, department, and job type. Findings revealed one-fifth of jobs advertised to be entry level, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 14 publications
0
25
0
1
Order By: Relevance
“…A new librarian's sense of isolation is exacerbated by the very competitive market for entry-level librarian positions. In a study of available entry-level positions within the US, Tewell (2012) found that there are a "small number of jobs that recent graduates can viably apply for" (421). This is due to the high number of applicants for a low number of entry-level postings, which means that successful candidates are "more likely to have several years of previous experience in libraries" (420).…”
Section: Precarious Labour In New Librarianshipmentioning
confidence: 99%
“…A new librarian's sense of isolation is exacerbated by the very competitive market for entry-level librarian positions. In a study of available entry-level positions within the US, Tewell (2012) found that there are a "small number of jobs that recent graduates can viably apply for" (421). This is due to the high number of applicants for a low number of entry-level postings, which means that successful candidates are "more likely to have several years of previous experience in libraries" (420).…”
Section: Precarious Labour In New Librarianshipmentioning
confidence: 99%
“…Un grand nombre d'entre elles se concentrent exclusivement sur la disponibilité des emplois à temps plein. En outre, la plupart visent à recenser les postes affichés à l'échelle nationale, car les emplois à temps partiel peuvent ne pas être suffisamment valorisés pour qu'on y consacre le temps et souvent l'argent nécessaires à les publier à plus grande échelle (Tewell 2012 …”
Section: Deuxième Projet De Rechercheunclassified
“…population growth generates openings (U.S. Department of Labor & Bureau of Labor Statistics, 2012, 2013. However, it should be noted that this optimistic prediction is reminiscent of the early 2000s expectation that the availability of academic library jobs would increase "due in large part to the 'graying' of the profession" (p. 408), an estimation that never came to fruition because budget constraints, especially in local government and educational services, slowed demand for librarians (Tewell, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The academic library job market for recent LIS graduates is competitive, and for those lacking significant practical experience, it is a "potentially insurmountable challenge" (p. 422) (Tewell, 2012). Nearly threequarters of academic librarian positions in 2011 preferred or required work experience (Triumph & Beile, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation